ANALYSIS OF THE ROLE OF REGIONAL GOVERNMENTS ON INDONESIAN INTERNATIONAL TRADE - Dwi Fauziansyah Moenardy; Gilang Nur Alam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Paradiplomacy with the involvement of local governments as actors in trade is a real demand in facing Indonesia’s competitiveness in facing the international trade climate. By increasing Indonesia’s trade with partner countries with the largest potential market in the world, in the form of implementation, the state needs the participation of various parties to be involved, including the Regional Government. With autonomy, regions can be involved in international trade. The purpose of this study is to determine the extent of the role of local governments in Indonesia’s international trade. This research is a descriptive analysis using qualitative research methods. The results of this study indicate that local governments play a role as international trade actors in carrying out regional potential promotion media and preparing strategies to increase the competitiveness of regional entrepreneurs through developing UMKM. With this, Paradiplomacy by involving local governments in the trade sector can become part of Indonesia’s foreign policy strategy to achieve success in the trade sector.